PENGUMBIAN IN VITRO KENTANG GRANOLA - Elfiani Elfiani (DINAMIKA PERTANIAN, 2013)
Potato production in Indonesia in 2008 reached 1.071 million tonnes or an increase of 6,7% compared to 2007 with a degree of productivity of 16,7 ha. However, the potato production can only meet the national requirement of 8%. The use of tissue culture techniques have been developed to produce seeds potato in large quantities; a short time, free of pests and virus diseases, and not depending on the season. This research aims to study the influence of media on the induction of shoots and tubers of potato in vitro using explants node and MS, CAP, BA 0.5, 1.0, 1.5, 2.0 ppm as media, implemented at tissue culture laboratory, IPB Bogor in 2010. The number of buds on the tuber formation of potato tissue culture result are obtained on the provision of the highest concentration of BA with 0.5 ppm, which is 13.6. BA concentration is a concentration equilibrium in the formation of buds. Height of shoots and the highest number of node available on the CAP administration respecticvely 6.1 and 36.